Turkish Olive Branch Operation’s Effect on Syria’s National Security Stability in 2018 - Ida Susilowati; Mohammad Latief; Zaenal, Zakliyyah Widad; Savira Maulida (Jisiera: The Journal of Islamic Studies and International Relations, 2024)
On January 20, 2018, Turkey officially announced the launch of a military operation called Olive Branch Operation in the town of Afrin, northwestern Syria, within two months to sweep Afrin from Partiya Yekitiya Democrat (PYD) and Yekineyen Parastina Gel (YPG) forces. However, the operation has affected Syiria’s national security stability based on the direct territorial line between the two sovereignties. This paper explains how the Olive Branch Operation influenced Syria's national security stability throughout 2018 using the concept of national security by Barry Buzan. The qualitative research method, analytical descriptive writing techniques, was used in this paper. This research concluded that the Turkish Olive Branch Operation hurt the stability of Syria's national security in 2018. It is based on several military, political, economic, social, and environmental indicators that occurred from this military operation toward the stability of Syria’s national security.